Peran Guru dalam Membentuk Karakter Religius Siswa melalui Pembelajaran Akidah Akhlak di MI Al-Hikmah - nofa, Alincia Nodika; Maryasyah; Nofa Dwijayanti; Tiara Nurhayati (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
Moral values education is a very important religious foundation that must be instilled in children from an early age; in elementary schools, this moral education has been incorporated into Islamic religious education lessons. This is in line with the purpose of education, which is to develop students into individuals who are devoted to God Almighty and have noble character. Educators play an important role in shaping students' religious character during the teaching and learning process. One of the factors that enhance students' character growth is the presence of Akidah Akhlak education at school. Akidah Akhlak lessons are very important in strengthening one's identity as a Muslim who embodies the qualities of a believer. Therefore, this study seeks to explore the influence of teachers in developing students' religious character through learning Akidah akhlak. This research uses a field study technique using qualitative methodology. Data collection techniques used in this study include observation, interviews, and documentation. The location of this research is MI Al-Hikmah Pagar Alam City. The findings of this study indicate that 1) Educators not only act as teachers, but also as role models in attitude and behavior, 2) Religious principles are instilled through consistent and exemplary practices, 3) Akidah Akhlak education is taught contextually and in accordance with student life, 4) Despite the challenges of globalization and the lack of external assistance, the role of teachers remains crucial. By teaching Akidah Akhlak, subject teachers instill character values in students and create a positive influence.